Development of Green Skills as an Educational Platform .......... 243 - Szczygieł, Elżbieta; Szyja, Paulina; Kowalska, Katarzyna; Śliwa, Renata (Fundamental Rights and Climate Change: Exploring New Perspectives and Corresponding Remedies, 2025)
Background: A perception of the possible impact of green skills development on society is presented. How have legislative and political processes of the EU been established in recent years to increase the importance and consciousness of individual participation in pro-ecological behaviours and given rise to the establishment of green skills to foster the care of the natural environment?Aim: The presentation will focus on the development of green skills as an educational platform to explore possible efforts to complement policy and/or regulatory adjustments.Method: The contributory character of the chapter is based on the three-fold axis of the analysis, encompassing political, legal perspective, and researching green skills as an effective platform to develop the cognitive perceptions of the solutions being recognised. The analysis is embedded in the review of the legal and political endeavours of the European Commission to grab the benefits of green transformation in the economic and political interest of all EU citizens, as well as on the perspective of the green skills development as an educational platform toward green transition.Research summary: The mix of legal, political or organisational as well as individual actions has the potential to stimulate activities that empower whole communities towards sustainable individual, public and corporate behaviour.